Fatty acids in different rapeseed varieties and their impact on human health - Mikołajczak, Natalia (Journal of Education, Health and Sport, 2018)
Introduction and aim: Rape is one of the most important oil plants grown all over the world. Oil obtained from rapeseeds has been dominating on the plant oil market for years, both in terms of production and consumption. It is considered the healthiest plant oil of all currently available. The purpose of this article was to review the available literature on the share of fatty acids in seeds of winter and spring rape, as well as to determine the impact of these fatty acids on the human body. Brief description of the state of knowledge: The collected data clearly indicated that rapeseed fat is a valuable source of unsaturated fatty acids, in particular monounsaturated acid (63 (spring rape) - 66% (winter rape)) and acids from omega-3 family (8.89 (pollinated varieties) - 9.35% (winter varieties)) and omega-6 family (16.35 (spring varieties) - 19% (hybrid varieties)). Rapeseed fat was also characterized by low share of saturated fatty acids (6.67 (winter varieties) - 11% (spring varieties)). Summary: Based on the literature review, it was found that rapeseed fat is a valuable source of unsaturated fatty acids (on average 92%), in particular C18:1 acid. In addition, share of C18:2 and C18:3 is also high, where the ratio of omega-6 and omega-3 is 2:1. The share of saturated fatty acids is relatively low (on average 8%). In addition, it can be concluded that the variety as an important factor determining the fatty acids composition of rapeseeds. The seeds of spring varieties are characterized by a higher share of saturated acids, and the seeds of winter varieties are more abundant in unsaturated acids. The highest share of C18:1 acid states for winter and pollinated varieties, C18:2 for hybrid varieties and C18:3 for winter varieties.